2018
DOI: 10.1002/advs.201800714
|View full text |Cite
|
Sign up to set email alerts
|

Phototunable Biomemory Based on Light‐Mediated Charge Trap

Abstract: Phototunable biomaterial‐based resistive memory devices and understanding of their underlying switching mechanisms may pave a way toward new paradigm of smart and green electronics. Here, resistive switching behavior of photonic biomemory based on a novel structure of metal anode/carbon dots (CDs)‐silk protein/indium tin oxide is systematically investigated, with Al, Au, and Ag anodes as case studies. The charge trapping/detrapping and metal filaments formation/rupture are observed by in situ Kelvin probe forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 57 publications
2
100
0
Order By: Relevance
“…The significant enhancement in the switching performance of SF memristors after AgNC meso‐functionalization can be understood as follows: as illustrated in Figure b, the switching performance of SF memristors is attributed to the formation and rupture of conductive paths . As shown in Figure S16 in the Supporting Information, the anodic dissolution of Ag occurs according to the reaction Ag→ Ag + + e − when a positive bias is applied to the Ag electrode and Ag ions migrate across the mediating protein layer.…”
Section: Resultsmentioning
confidence: 97%
“…The significant enhancement in the switching performance of SF memristors after AgNC meso‐functionalization can be understood as follows: as illustrated in Figure b, the switching performance of SF memristors is attributed to the formation and rupture of conductive paths . As shown in Figure S16 in the Supporting Information, the anodic dissolution of Ag occurs according to the reaction Ag→ Ag + + e − when a positive bias is applied to the Ag electrode and Ag ions migrate across the mediating protein layer.…”
Section: Resultsmentioning
confidence: 97%
“…The EFM measurement, coupled with KPFM result suggest that the hole concentration of InP/ZnS QD film will increase under light illumination (Figure S14 in the Supporting Information). [ 64–67 ] Then, to theoretically investigate the charge transition mechanism, we adopted a simple model to evaluate the excitation behaviors of electron‐hole pairs in the InP/ZnS QDs. The wavefunctions and eigenenergies of electrons and holes for InP/ZnS core/shell QDs were evaluated by treating them as independent particles confined in spherical wells with finite depth.…”
Section: Resultsmentioning
confidence: 99%
“…This decrease in Schottky barrier caused development of quasi-ohmic contact, which corresponded to LRS. [156] These results suggest a novel structure to realize photonic synapse which is based on OIP quantum dots. This study also showed "OR" logic, and coincidence event detection.…”
Section: Light-stimulated Memory Device and Logic Applicationsmentioning
confidence: 88%